Differences in Arbuscular Mycorrhizal Fungi among Three Coffee Cultivars in Puerto Rico. (15th August 2012) - Lebrón, Ligia; Lodge, D. Jean; Bayman, Paul
Abstract : Mycorrhizal symbiosis is important for growth of coffee ( Coffea arabica ), but differences among coffee cultivars in response to mycorrhizal interactions have not been studied. We compared arbuscular mycorrhizal (AM) extraradical hyphae in the soil and diversity of AM fungi among three coffee cultivars, Caturra, Pacas, and Borbón, at three farms in Puerto Rico. Caturra had significantly lower total extraradical AM hyphal length than Pacas and Borbón at all locations. P content did not differ among cultivars. Extraradical hyphal lengths differed significantly among locations. Although the same morphotypes of mycorrhizal fungal spores were present in the rhizosphere of the three cultivars and total spore density did not differ significantly, frequencies of spore morphotypes differed significantly among cultivars. Spore morphotypes were typical of Glomus and Sclerocystis . Levels of soil nutrients did not explain differences in AM colonzation among cultivars. The cultivar Caturra is a mutant of Borbón and has apparently lost Borbón's capacity to support and benefit from an extensive network of AM hyphae in the soil. Widespread planting of Caturra, which matures earlier and has higher yield if fertilized, may increase dependence on fertilizers.